2022
DOI: 10.1186/s42826-022-00122-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of instillation of MB49 cells and thermoreversible polymeric gel in urothelial bladder carcinoma immunization

Abstract: Background Activating the immune system for therapeutic benefit has long been a goal in immunology, especially in cancer treatment, but the low immunogenicity of antitumor vaccines remains a limiting factor in the fight against malignant neoplasms. The increase in the immunogenicity of weak antigens using biodegradable polymers, such as chitosan, has been observed in the field of cancer immunotherapy. However, the effects of the vaccine using a combination of tumor cells and a thermoreversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Animals immunized with the TPGþMB49 vaccine showed higher cumulative survival rates, significantly reduced bladder weight and size compared to the other groups (Fig. 1) [19]. This revealed that incorporation of MB49 cells into the chitosan-based thermos-reversible polymeric gel matrix and using it as an intravesical vaccine can trigger immune responses and slow the growth of bladder tumors in vivo [19].…”
Section: Advancement Of Immunotherapy For Treatment Of Bcmentioning
confidence: 93%
See 4 more Smart Citations
“…Animals immunized with the TPGþMB49 vaccine showed higher cumulative survival rates, significantly reduced bladder weight and size compared to the other groups (Fig. 1) [19]. This revealed that incorporation of MB49 cells into the chitosan-based thermos-reversible polymeric gel matrix and using it as an intravesical vaccine can trigger immune responses and slow the growth of bladder tumors in vivo [19].…”
Section: Advancement Of Immunotherapy For Treatment Of Bcmentioning
confidence: 93%
“…Recent progress in cancer immunotherapy suggests that biodegradable polymers such as chitosan could enhance the effectiveness of weak antigens [19]. The feasibility of this was evidenced by a recent study, which assessed the effectiveness of a polymeric gel matrix (TPG) consisting of poloxamer 407 and chitosan, along with MB49 cells, as an intravesical anticancer vaccination in a C57BL/6 mouse model of bladder urothelial carcinoma [19]. The efficacy of vaccination was evaluated by dividing mice into three groups: control, TPG, and TPGþMB49.…”
Section: Advancement Of Immunotherapy For Treatment Of Bcmentioning
confidence: 99%
See 3 more Smart Citations